2019
DOI: 10.1103/physreve.100.012144
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of driven autocatalytic reactive mixtures

Abstract: Motivated by the theory of reaction kinetics based on nonequilibrium thermodynamics [1] and the linear stability of driven reaction-diffusion[2], we apply the Fokker-Planck equation to describe the population dynamics of an ensemble of reactive particles in contact with a chemical reservoir. We illustrate the effect of autocatalysis on the population dynamics by comparing systems with identical thermodynamics yet different reaction kinetics. The dynamic phase behavior of the system may be entirely different fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…for LFP [18][19][20] or graphite. 21 A more consistent and accurate approach is to use phase-field models, [22][23][24][25][26][27] generalized for electrochemical thermodynamics 28 of single particles 23,[29][30][31][32][33][34][35][36][37][38][39] and porous electrodes, [40][41][42][43][44][45] but a clear classification of the possible nonequilibrium phase morphologies has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…for LFP [18][19][20] or graphite. 21 A more consistent and accurate approach is to use phase-field models, [22][23][24][25][26][27] generalized for electrochemical thermodynamics 28 of single particles 23,[29][30][31][32][33][34][35][36][37][38][39] and porous electrodes, [40][41][42][43][44][45] but a clear classification of the possible nonequilibrium phase morphologies has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it has been shown that by understanding the functional form of the reaction rate expressions, one is able to control, and consequently engineer, the physics of interfaces where reactions take place [26]. Representative examples are the lithiation of LFP and LiNi 1/3 Mn 1/3 Co 1/3 O 2 [149,150] particles, as well as the operation of Li-air batteries, where the thermodynamic stability of the system is controlled by varying the applied current [13,95,102,151,152]. In terms of CIET, by understanding the concentration dependencies of both the reorganization energy and the density of states of the electron donor, we will be able to control interface structure by inducing or suppressing phase separation/island formation.…”
Section: Discussionmentioning
confidence: 99%
“…[173] Such a phase-separation phenomenon is a source of instability in a population of particles which undergo particle-byparticle separation, also known as mosaic instability. [174] This can sometimes result in a bimodal distribution of the state of lithiation throughout the electrode at low charge/discharge rates, as experimentally visualized in LFP [175,176] and graphite [58] and then explained by physics-based theories. [60,173,174,177,178] Compositional heterogeneities have been reported also in NMC and nickel cobalt aluminum oxide (NCA), [179][180][181] both at high C-rates, [181] which can be induced by autocatalytic reaction kinetics, [182] and in agglomerate particle as a consequence of internal stress.…”
Section: Prediction Of Electrochemical Propertiesmentioning
confidence: 99%
“…[174] This can sometimes result in a bimodal distribution of the state of lithiation throughout the electrode at low charge/discharge rates, as experimentally visualized in LFP [175,176] and graphite [58] and then explained by physics-based theories. [60,173,174,177,178] Compositional heterogeneities have been reported also in NMC and nickel cobalt aluminum oxide (NCA), [179][180][181] both at high C-rates, [181] which can be induced by autocatalytic reaction kinetics, [182] and in agglomerate particle as a consequence of internal stress. [183,184] There exist at least two consolidated theories to model phaseseparating materials, namely the sharp interface model and the phase-field model.…”
Section: Prediction Of Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation